OCCUPATIONAL HEARING LOSS: A CROSS-SECTIONAL SURVEY IN A MANUFACTURING INDUSTRY AT BAHAWALPUR - Khan, Muhammad Ahmed; Akram, Sumera; Majeed, Shahid; Bin Usman, Hassan (Journal of Postgraduate Medical Institute, 2016)
Objective: To assess occupational hearing loss among the workers of a manufacturing industry at Bahawalpur. Methodology: This cross sectional study was carried out in a manufacturing industry in Bahawalpur. The study was carried out from August to October 2015. There were 448 individuals working in that industry. All those individuals who were subject to daily noise in the industry and who consented for inclusion in the study were included. Information including age, gender, use of protective ear plugs, and history of any chronic disease or chronic drugs/ medications use was also gathered. A qualified audiologist carried out pure tone audiometry (PTA) of all the workers in standard settings. Results: Pure tone audiometry (PTA) of 448 industry workers showed that 39(8.71%) had sensorineural hearing loss and 8(1.78%) had conductive hearing loss. Among 39 patients of sensorineural hearing loss, 29 had mild (from 26 to 40 dB), 7 had moderate (from 41 to 55dB) and 3 had moderately severe (56 to 70dB) hearing loss. When enquired about use of hearing protection devices during noise exposure, 30 of these 39 did not use hearing protection devices while 9 used hearing protection measures, showing significant association between use of hearing protection device and healthy hearing (p=0.000). Out of 448 workers, 367(81.92%) used the hearing protection devices and rest 811(8.08%) denied their use. Conclusion: Occupational noise can lead to hearing loss. Use of hearing protection measures are significantly associated with healthy hearing.